Mycobiomes of two distinct clades of ambrosia gall midges (Diptera: Cecidomyiidae) are species-specific in larvae but similar in nutritive mycelia - Pyszko, Petr; Šigutová, Hana; Kolařík, Miroslav; Kostovčík, Martin; Ševčík, Jan; Šigut, Martin; Višňovská, Denisa; Drozd, Pavel (Microbiology spectrum, 2024)
Ambrosia gall midges are endophagous insect herbivores whose larvae live enclosed within a single gall for their entire development period. They may exhibit phytomycetophagy, a remarkable feeding mode that involves the consumption of plant biomass and mycelia of their cultivated gall symbionts. Thus, AGMs are ideal model organisms for studying the role of microorganisms in the evolution of host specificity in insects. However, compared to other fungus-farming insects, insect-fungus mutualism in AGMs has been neglected. Our study is the first to use DNA metabarcoding to characterize the complete mycobiome of the entire system of the gall-forming insects as we profiled gall surfaces, nutritive mycelia, and larvae. Interestingly, larval mycobiomes were significantly different from their nutritive mycelia, although Botryosphaeria dothidea dominated the nutritive mycelia, regardless of the evolutionary separation of the tribes studied. Therefore, we confirmed a long-time hypothesized paradigm for the important evolutionary association of this fungus with AGMs.
Keywords: hmyz; larva; mykobiom; fungiculture; Asphondylia; zvířata; Ambrosia; Insecta; nutritive mycelium; larval mycobiome; ambrosia gall midge; phytomycetophagy; Diptera; Lasioptera; Mycobiome; metabarcoding; Cecidomyiidae; Larva; Animals